Frequency of Wound Infection and Common Factors Leading to it Among Patients Undergoing Cesarean Section - Zubair, Maryam (International Journal of Pathology, 2020)
Background: Surgical site infections (SSI) account for about 20% of all hospital acquired infections. The etiology of wound infection is polymicrobial.Objectives: The present study was conducted to determine the frequency of wound infection and common factors leading to it among patients after cesarean section.Methods: Descriptive (cross-sectional) study was conducted from December 2017 to December 2018 at the Department of Obstetrics & Gynaecology Sheikh Khalifa Bin Zayad Hospital Muzaffarabad. Sample was collected through non probability consecutive sampling.205 patients who were fulfilling the inclusion criteria were enrolled in the study. All patients were followed up to7th postoperative day for wound infection and risk factors were noted. Data was collected on a pre-designed Performa including demography, gravidity, parity wound infection and risk factors. Data was analyzed by using SPSS version 20.Results: A total of 205 postoperative patients were recorded during the study period. The frequency of wound infection was calculated as 13(6.3%). The common factors leading to wound infection were prolonged labor in 16patients(7.8%), anemia 70 patients(34.1%), prolonged rupture of membranes 15 patients(7.3%) and chorioammionitis 2patients(1.0%).Mean age of the patients was 29.02±6.102, gravidity 2.42±1.485 and parity was calculated as 1.32±1.409.Conclusions: The study concludes that the frequency of wound infection in this setting is in keeping with globally cited frequencies. Other findings such as causes of wound infection and maternal morbidity data also agree with most national and international studies on this topic.